2017
DOI: 10.1016/j.jpeds.2017.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplantation for FLNA -Associated Progressive Lung Disease

Abstract: OBJECTIVE To review the outcome of patients with pathogenic variants in FLNA and progressive lung disease requiring lung transplantation. STUDY DESIGN We conducted a retrospective chart review of six female infants with heterozygous presumed loss of function pathogenic variants in FLNA whose initial presentation was early and progressive respiratory failure. RESULTS Each patient received lung transplantation at an average age of 11 months (range: 5 to 15 months). All patients had pulmonary arterial hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 35 publications
2
38
0
6
Order By: Relevance
“…Therapy with bronchodilatatorFemaleDeletion c.2190_2193delTTAC (p.Tyr731Alafs*10)Viral infectionsRight upper and middle, left upper lobe over-inflation; Coarse septal thickening; Lower lobe atelectasis383 monthsNoneNot performedAge 6 years. Supplementary oxygen supportBurrage et al, 2017 [14]FemaleDuplication c.4596dupG (p.Ser1533Glufs*12)Progressive lung diseaseIn all patients, severe pulmonary hyperinflation and hyperlucency with peripheral pulmonary vascular attenuation with parahilar and dependent lower lobe atelectasis and central pulmonary artery enlargement.In all patient, pulmonary arterial hypertension was also diagnosed.392–4 monthsPDA ligationYesLung transplantation in all.Five survivors at 19 months, 3 years, 4 years, 5.1 years, and 11.3 years respectively, post- follow-up. One died at 3 yearsFemaleMissense mutationc.5290G > A (p.Ala1764Thr)Progressive lung disease40neonatalPDA ligationYesFemaleDuplication c.4446_4447dupAT (p.Leu1483Tyrfs*19)Progressive lung disease38neonatalPDA ligationYesFemaleDuplication c.4617_4618delGC (p.Leu1540Alafs*4)Progressive lung disease34neonatalPDA ligationYesFemaleDuplication c.6585dupT (p.Pro2196Serfs*3)Progressive lung disease39neonatalPDA ligationYesFemaleMissense mutation c.2807A > G (p.Lys936Arg)Progressive lung disease38neonatalPDA ligationYesKinane et al 2017 [15]FemaleDeletion c.6577delC (p.Arg2193Alafs*14)Diffuse pulmonary abnormalitiesGround glass opacities, area of hyperacration, pulmonary hypertension3930 dayPDA ligationYesSasaki et al 2018 [16]FemaleDeletion c.1709_1712del (p.Val570Alafs*105)Progressive lung diseaseDiffuse bilateral groung-glass opacification throughout the lung, interstitial thickening, cystic changes371 monthNoneYesDied at 4 monthsMaleSplice site deletion c.6670-1delGSeveral episodes of profound desaturationBilateral dependent and subsegmental atelectasis, scattered opacity, interstitial thickening32day of live 1NoneYes…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Therapy with bronchodilatatorFemaleDeletion c.2190_2193delTTAC (p.Tyr731Alafs*10)Viral infectionsRight upper and middle, left upper lobe over-inflation; Coarse septal thickening; Lower lobe atelectasis383 monthsNoneNot performedAge 6 years. Supplementary oxygen supportBurrage et al, 2017 [14]FemaleDuplication c.4596dupG (p.Ser1533Glufs*12)Progressive lung diseaseIn all patients, severe pulmonary hyperinflation and hyperlucency with peripheral pulmonary vascular attenuation with parahilar and dependent lower lobe atelectasis and central pulmonary artery enlargement.In all patient, pulmonary arterial hypertension was also diagnosed.392–4 monthsPDA ligationYesLung transplantation in all.Five survivors at 19 months, 3 years, 4 years, 5.1 years, and 11.3 years respectively, post- follow-up. One died at 3 yearsFemaleMissense mutationc.5290G > A (p.Ala1764Thr)Progressive lung disease40neonatalPDA ligationYesFemaleDuplication c.4446_4447dupAT (p.Leu1483Tyrfs*19)Progressive lung disease38neonatalPDA ligationYesFemaleDuplication c.4617_4618delGC (p.Leu1540Alafs*4)Progressive lung disease34neonatalPDA ligationYesFemaleDuplication c.6585dupT (p.Pro2196Serfs*3)Progressive lung disease39neonatalPDA ligationYesFemaleMissense mutation c.2807A > G (p.Lys936Arg)Progressive lung disease38neonatalPDA ligationYesKinane et al 2017 [15]FemaleDeletion c.6577delC (p.Arg2193Alafs*14)Diffuse pulmonary abnormalitiesGround glass opacities, area of hyperacration, pulmonary hypertension3930 dayPDA ligationYesSasaki et al 2018 [16]FemaleDeletion c.1709_1712del (p.Val570Alafs*105)Progressive lung diseaseDiffuse bilateral groung-glass opacification throughout the lung, interstitial thickening, cystic changes371 monthNoneYesDied at 4 monthsMaleSplice site deletion c.6670-1delGSeveral episodes of profound desaturationBilateral dependent and subsegmental atelectasis, scattered opacity, interstitial thickening32day of live 1NoneYes…”
Section: Discussionmentioning
confidence: 87%
“…Perinatal lethality occured in six of these reported cases (24%; 5 females and 1 male); in all cases, cardiopathies were also found [2–10, 1315, 18]. As reported in Table 1, a large spectrum of FLNA mutations are detected in patients with pulmonary disease, including missense mutations [9, 13, 14, 19], nonsense mutations [2, 20], deletions [13, 15, 16, 21], duplications [13, 14, 18, 21], truncating mutations [17, 21], and frameshift mutations [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is emerging recognition of a respiratory phenotype of this genetic disorder that occurs in infancy and has unique features, including cardiovascular manifestations (aortic-valve disease and dilatation, patent ductus arteriosus, and pulmonary hypertension) and pulmonary manifestations (emphysema and lung cysts alternating with atelectasis and tracheobronchomalacia or stenosis). [14][15][16][17][18][19][20][21] A recent review summarizes the cases reported in the literature to date. 22 Thus far, at least 18 cases of FLNA-related disease with this respiratory phenotype have been identified in infancy.…”
Section: Connective-tissue Disordersmentioning
confidence: 99%
“…20 Since then, 17 additional case reports of lung disease have been described in the literature, but more cases are being recognized in the clinic, particularly in lung transplantation centers. [15][16][17][18][19][20][21][22]27 Of the 18 patients, 15 were female, which suggests that males are more likely to be severely affected and are less likely to survive to birth. All but 1 of these patients were born at full term.…”
Section: Agnos Tic Tes Tingmentioning
confidence: 99%